Nano iron pyrite (FeS2) exhibits bi-functional electrode character. Issue 20 (9th February 2016) - Dubey, Amarish; Singh, Sushil Kumar; Tulachan, Brindan; Roy, Manas; Srivastava, Gaurav; Philip, Deepu; Sarkar, Sabyasachi; Das, Mainak
Abstract : Sustainable charge storage devices require materials that are environmentally benign, readily moldable, easily synthesizable, and profitable for applications in the electronics industry. Abstract : Sustainable charge storage devices require materials that are environmentally benign, readily moldable, easily synthesizable, and profitable for applications in the electronics industry. Nano iron pyrite (FeS2 ) is one such material, which is applicable in diverse areas like photovoltaic devices to seed dressing in agriculture. In this work, we propose an innovative application of nano FeS2 viz., as a symmetric charge storage device that is flexible, portable, and lightweight; along with its fabrication details. The device consists of a (H3 PO4 )/polyvinyl alcohol (PVA) electrolyte gel sandwiched between two similar electrodes made up of FeS2 /poly-aniline (PA), upon which graphite sheets are used as current collectors. Electrodes were characterized by XRD, FTIR and SEM. The device was calibrated by cyclic voltammetry and charge–discharge cycle. In its present laboratory prototype form, it powers solid-state electronic devices and electric motors. Further refinements of this device will open up new avenues in the field of sustainable charge storage devices and low power electronics.